Estudo da fenotipagem de quatro enzimas metabolizadoras de fármacos em uma amostra da população do estado do Ceará - Santana, Gilmara Silva de Melo (2004)
Characterization of acetylator and oxidative metabolizers phenotypes is of clinical relevance, as it has been shown that the pharmacological response of several therapeutic agents. The studies of phenotypage and genotipage have as purpose to detect and to mensurar polimorfismos in these enzymes. In this study, we assessed in vivo activities of CYP1A2, CYP2A6, Xantine Oxidase (XO) and NAT2 in sample of 82 volunteers (40 men and 42 women) from Ceará – Brazil using caffeine as probe. The volunteers were free from significant cardiac, hepatic, renal, pulmonary, gastrointestinal and hematological disease, as assessed by physical investigation, ECG and hematological and biochemical tests. The study was open, the volunteers were hospitalized, having already had a normal evening meal, and after an overnight fast they received a single 200 mg dose of caffeine tablet. Blood samples were collected in regular interview ( 0; 5min; 15min; 25min; 35min; 45min; 1h; 1,25h; 1,5h; 2h; 4h; 6h; 8h; 12h and 24 hour) after the administration of caffeine. Urine was harvested in its total volume during the 10 hours after the administration of caffeine, the total urinário volume was quantified and an aliquot one was stored for determination of the metabólitos. The caffeine was determined in human plasma and the metabolites were determined in human urinary by HPLC using teobromina as an internal standard. The metabolites assessed were: 1U – 1-methyluric acid; 17U – 1, 7-dimethyluric acid; 1X – 1-methylxantine; 17X – 1, 7-1-dimethylxantine e AFMU – 5-acetylamino-6-formylamino-3methyluracil. The following molar ratios were calculated as an index for CYP1A2 activity [(AFMU + 1X + 1U)/ 17U]; CYP2A6 activity [17U / (AFMU + 1X + 1U + 17X + 17U)]; NAT2 activity [AFMU/ (AFMU + 1X + 1U)] and Xanthine Oxidase activity [1U/ (1X + 1U)]. The enzymatic activities were plotted in histogram. The frequency distributions of the CYP1A2, CYP2A6, XO and NAT2 were not normally distributed, showing three phenotypes. Afterwards the volunteers were classified by enzymatic activities in ten groups, and the lowest and highest metabolizers groups were chosen to determine the following pharmacokinetic parameters: AUC0-24, t1/2, ke, CL and Vd/Kg. The comparison of these parameters (test “t” de Student) between these two groups it showed significant differences (p<0.05). Our findings may suggest that the heterogeneous population assessed (health volunteers from Ceará - Brazil) has shown polymorphism in the enzymatic activities of the CYP1A2, NAT2, XO and CYP2A6.